In vitro effect of Citrullus Colocynthis and Acacia Radiana on Phosphate Calcium Crystallization - Mohamed, Beghalia; Belouatek, Aissa; Ghalem, Said; Allali, Hocine (Pharmacognosy Communications)
Introduction: In this work, we performed an in vitro crystallization study enabling the specification of kinetic and thermodynamic conditions of formation and growth of crystalline calcic phosphates species by changing the pH. We used inhibitors, which are medicinal plants which prevent, slow down or reduce crystallization phases. Materials and Methods: We chose the classical model for the study of phosphate crystallization without inhibitor and with it, in order to assess the inhibiting capacity of any chemical species used. The precipitation of the solid phase of phosphates from artificial urine at different initial pH values was the object of our investigation. The crystal size development was monitored by polarized microscopy at different time intervals. After crystallization time, the mixture was filtered, the recovered dried precipitates were analysed by FTIR. In the absence of inhibitor, the crystallization of phosphates at pH=8.00, led to the formation of struvite and Amorphous Carbonated Calcium Phosphates (ACCP), after 4 hours. In presence of inhibitor at pH=8.00 at lower concentrations of sage inhibition was partial. Result and Discussion: The addition of 1 ml of sage to the mixture decreases the size of crystal, after 4 hours the size of crystals stabilized at 20.67 μm. The complete disappearance of brushite crystals was obtained after addition of 10mL of Citrullus Colocynthis, only Pentahydrated octocalcic phosphates (POP) and ACCP were formed. In the presence of Acacia Radiana, the inhibition of struvite growth and aggregation increased. The addition of up to a volume of 20 mL of Acacia Radiana resulted in total inhibition and crystalline transformation of the ACCP into carbapatite (CA). Phosphate compounds encountered in urine can be dangerous and the use of inhibitors to prevent, slow down or reduce crystallization phases might be very helpful. Conclusion: In this investigation, Citrullus Colocynthis and Acacia Radiana proved to be good inhibitors. Their effect increases with solution pH but they are more efficient in less acidic or neutral urine than in alkaline one.
Keywords: Acacia Radiana; Citrullus Colocynthis; Crystallization; Inhibition; Struvite